Oligo-Carrageenans Enhance Growth and Contents of Cellulose, Essential Oils and Polyphenolic Compounds in Eucalyptus Globulus Trees - Moenne-Munoz, A; Contreras-Arredondo, R; Gonzalez-Figueroa, A (2013)
Sin Editorial Disponible